The Value of Customer Loyalty and Satisfaction in Antam’s Precious Metal Products (A Kano Model Analysis) - Rahmawati, Nur (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2020)
This researcher aims to map and analyze the customer loyalty and satisfaction of Antam's Precious Metal (LM) products through four categories of the Kano model. These include one dimensional or performance needs, must be or basic needs, attractive or excitement needs, and indifferent needs. This is a qualitative research with data obtained from interviews, observation and documentation. The study shows that the value of customer loyalty and satisfaction in Precious Metal products, referring to the Kano model analysis, is included in the one-dimensional or performance requirements. Here, the level of satisfaction is directly proportional to the performance attributes. This means that the performance attributes can affect the level of customer satisfaction. Pure Gold, as an Antam’s Precious Metal products, is not considered as must-be or basic needs. It is regarded as attractive or excitement needs due to the rapid development of PT. Antam which is strongly influenced by the quality and development of its product attributes, especially the precious metal products. This study proposes the formation of classification of customer satisfaction using the Kano model and customer loyalty so that it provides benefits in terms of the classification of customer satisfaction. AbstrakPenelitian ini bertujuan untuk memetakan dan menganalisis loyalitas dan kepuasan konsumen produk Logam Mulia (LM) Antam melalui empat kategori model Kano yaitu: one dimensional atau performance needs, must be atau basic needs, atractive atau excitement needs, dan Indifferent. Penelitian ini merupakan penelitian kualitatif dengan data yang diperoleh melalui wawancara, observasi dan dokumentasi. Hasil penelitian ini menunjukkan bahwa nilai loyalitas dan kepuaan konsumen pada LM Antam, perspektif model Kano, masuk pada kategori one dimensional atau performance needs. Ini berarti tingkat kepuasan berbanding lurus dengan kinerja atribut, sehingga berdampak pada tingginya kepuasan konsumen. Sedangkan emas LM Antam tidak masuk kategori must be atau basic needs, atractive atau excitement needs, dan Indifferent karena perkembangan pesat PT. Antam saat ini sangat dipengaruhi oleh kualitas dan perkembangan Atribut produk, khususnya pada LM Antam. Hasil penelitian tersebut berimplikasi pada terbentuknya klasifikasi kepuasan konsumen dengan menggunakan model Kano dan loyalitas konsumen. Hal ini memberikan manfaat dalam hal klasifikasi kepuasan konsumen.